Illuminating Museums. From Design to Experience - Viviana Gobbato (Ambiances)
This paper raises the possibility of museum lighting as a tool for ‘mediation’ within museums. It studies its functions in the process of interpreting, transmitting and receiving collections. Based on a comprehensive approach to design and experience, the author focuses specifically on three possible functions: ostensive function (to show space and artworks), cognitive function (to influence the construction of meaning and reasoning), and aesthetic function (to stimulate sensitive and contemplative states). To explore the mediating functions of lighting in both design and experience, she discusses the findings from several case studies (30 European museums), interviews with lighting designers and museum managers (54), as well as participant observations (4 months) and surveys on embodied cognition and experience (26). Three concepts emerge that could contribute to new research studies in the field of museology, specifically focusing on exhibition design and the visitor experience: ‘museum lighting design,’ ‘light sensory index’ and ‘luminous sensory mediation.’